Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu Menggunakan Model Problem Based Learning (PBL) di Sekolah Dasar - Wahyuni, Desri; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to improve the results of integrated thematic learning using the Problem based Learning model. This research is a classroom action research using qualitative and quantitative approaches. Conducted in two cycles, namely the first cycle of 2x meetings, and the second cycle of the 1x meeting. The subjects of the study were 24 students of fifth grade SDN 10 Sapiran Bukittinggi. The research data was obtained from the results of observations and sources of data obtained during learning. The results showed an increase. This can be seen from the average results in the first cycle of meetings 1 and 2, which obtained a class average of 74.46 (K) and the second cycle obtained a class average of 83.12 (B). It was concluded that using the PBL model was able to improve student learning outcomes in integrated thematic learning in class V. Keywords: